2018
DOI: 10.1016/j.bone.2017.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell inhibition as a therapeutic approach in fibrodysplasia ossificans progressiva (FOP)

Abstract: This work demonstrates that consideration of FOP as a type of localized mastocytosis may offer new therapeutic interventions for treatment of this devastating condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 33 publications
2
21
0
1
Order By: Relevance
“…(4) Our group further reported that inhibition of mast cell degranulation by cromolyn reduced HO formation. (11) These data support that mast cells are additionally integral to the development of HO.The overlapping inflammatory features among genetic and nongenetic HO disorders has increasingly been confirmed over recent years, and future studies will further clarify commonalities, such as the role of additional cytokines, macrophage polarization, and other immune cell contributions to HO formation. Although it is important to note the unique aspects of FOP pathology, including accelerated cartilage and bone cell differentiation caused by the R206H mutation, (12,13) we fully agree with Levesque and colleagues that the overlapping…”
supporting
confidence: 53%
See 1 more Smart Citation
“…(4) Our group further reported that inhibition of mast cell degranulation by cromolyn reduced HO formation. (11) These data support that mast cells are additionally integral to the development of HO.The overlapping inflammatory features among genetic and nongenetic HO disorders has increasingly been confirmed over recent years, and future studies will further clarify commonalities, such as the role of additional cytokines, macrophage polarization, and other immune cell contributions to HO formation. Although it is important to note the unique aspects of FOP pathology, including accelerated cartilage and bone cell differentiation caused by the R206H mutation, (12,13) we fully agree with Levesque and colleagues that the overlapping…”
supporting
confidence: 53%
“…(4) Our group further reported that inhibition of mast cell degranulation by cromolyn reduced HO formation. (11) These data support that mast cells are additionally integral to the development of HO.…”
mentioning
confidence: 61%
“…Also mast cells are massively present in early lesions from FOP patients and in those observed in an injury-mediated mouse model [ 67 , 73 ]. These tissues expressed increased levels of Substance P, a known potent neuro-inflammatory factor, as a consequence of the dysregulated BMP pathway.…”
Section: Targeting the Immune Systemmentioning
confidence: 99%
“…Récemment, des travaux ont démontré que l'inhibition des mastocytes pouvait diminuer fortement les formations osseuses hétérotopiques dans un modèle murin de fibrodysplasie ossifiante progressive (FOP, ou maladie de l'homme de pierre), une maladie congénitale rare caractérisée par la transformation des tissus mous (tendons, muscles, ligaments) en os. Aucun traitement n'existe aujourd'hui contre la FOP et la considérer comme une mastocytose localisée pourrait offrir des possibilités thérapeutiques aux patients dans le futur [17]. Les mastocytes font également partie des nombreux types cellulaires qui sont présents au sein, ou à proximité, des tumeurs, dont ils pourraient favoriser la croissance par leurs propriétés pro-angiogéniques et pro-lymphangiogéniques [18].…”
Section: Histamineunclassified